Lack of antigenic diversification of major outer membrane proteins during clonal waves of Neisseria meningitidis serogroup A colonization and disease - Huber, Charlotte A.; Pflüger, Valentin; Hamid, Abdul-Wahab M.; Forgor, Abudulai A.; Hodgson, Abraham; Sié, Ali; Junghanss, Thomas; Pluschke, Gerd (Pathogens and disease, 2013)
In particular in the ‘meningitis belt’ of sub-Saharan Africa, epidemic meningococcal meningitis is a severe public health problem. In the past decades, serogroup A lineages have been the dominant etiologic agents, but also other serogroups have caused outbreaks. A comprehensive vaccine based on subcapsular outer membrane proteins (OMPs) is not available. Here, we have investigated whether meningococcal populations overcome herd immunity by changing antigenic properties of their OMPs. Meningococcal isolates were collected in the context of longitudinal studies in Ghana between 2002 and 2008 and in Burkina Faso between 2006 and 2007. Serogroup A strains isolated during two clonal waves of colonization and disease showed no diversification in the genes encoding their PorA, PorB, and FetA proteins. However, we detected occasional allelic exchange of opa genes, as well as wide variation in the number of intragenic tandem repeats, showing that phase variation of Opa protein expression is a frequent event. Altogether we observed a remarkable antigenic stability of the PorA, PorB and FetA proteins over years. Our results indicate that while herd immunity may be responsible for the disappearance of meningococcal clones over time, it is not a strong driving force for antigenic diversification of the major OMPs analyzed here.
Gesehen am 02.11.2021